(untitled) (Diametros, 2023)
The following text is a voice in the discussion around normative problems of innovative therapies. It particularly refers to the meaning of the concept of innovation, also discussed in this issue in the article by Tomasz Rzepiński "Advanced therapy medicinal products (ATMP) as products of innovative biotechnologies."